Site scale landslide deformation and strain analysis using MT-InSAR and GNSS approach – A case study. Issue 12 (15th December 2022) - Kumar Maurya, Vipin; Dwivedi, Ramji; Ranjan Martha, Tapas
Abstract: Surface deformation monitoring plays a vital role in understanding landslide kinematics and slope failure analysis. In the past, applications of precise geodetic techniques have been successfully demonstrated for surface deformation analysis in natural hazard monitoring. This study presents, first of its kind in India, site-scale deformation analysis of a half-century old active landslide (Jaggi Bagwan) in Rudraprayag district, Uttarakhand state (India). We present an approach to investigate the spatial variability of surface deformation (i.e. sectors with different kinematics within a landslide) using multi-temporal interferometric Synthetic Aperture radar (MT-InSAR) derived strain map. The maximum negative mean displacement rates obtained by MT-InSAR processing of 30 Ascending and 32 descending Sentinel-1A scenes are 27.56 mm/yr and 1.11 mm/yr, respectively. It indicates the presence of instability at the study site which is further supported by a line of sight (LOS) projected Global Navigation Satellite System (GNSS) displacement rates. Subsequently, a modified least square method is applied to generate strain map using 3D velocity components obtained by multi-geometry LOS decomposition. The interpretation of strain map is further assisted by the instabilities observed at the crown of Jaggi Bagwan using Google Earth imageries from 1996 to 2018 to better correlate the strain pattern. Strain rate map clearly identified the sectors with dominating extension and compression within landslide. The presented approach can be further extended to landslide risk reduction along national highways and valley blockages.